Physico-Chemical and Biological Water Quality of Tuntang Estuary, Demak, Central Java as A Base for Sustainable River Management - Danurrachman, Y.; Maryono, M.; Muhammad, F.; Soeprobowati, T. R.; van der Maas, P. (Jurnal Pendidikan IPA Indonesia, 2023)
The estuary, downstream of the river, accumulates pollutants from upstream and marine. Tuntang is one of the major rivers in Central Java, 139 km length from Rawapening Lake, and ends in the Java Sea. Mangroves are the dominant riparian vegetation in the downstream and estuary of the Tuntang River. This research analyzes the water quality and pollution index (PI) of Tuntang Estuary, Demak. Water samples were collected from four sites in February (wet season) and September 2022 (dry season) and were analyzed for temperature, TDS, pH, BOD, COD, DO, nitrate, nitrite, ammonia, TN, TP, Cd, Cu, Pb, Cr, fecal coliform, and total coliform. The water quality parameters of Tuntang Estuary in the dry season exceeded the threshold for Class I-III, such as TDS in T1 ((2530 mgL-1), BOD (4.06-5.12 mgL-1), COD (28.32-102 mgL-1), DO for Class I and II (3.93-4.28 mgL-1), Pb at T1 and T3 in the wet season, and T1 in the dry season, and Cr for Class I, II, and III (. 0.05 mgL-1), Pb (T1), and Cr for Class I, II, and III (. 0.05 mgL-1). In contrast, in the wet season, BOD (4.37-7.15 mgL-1), Pb (T1 and T3), fecal coli, and coliform exceeded the threshold. The TN (0.83-2.48 mgL-1) and TP in the wet season (0.45-0.53 mgL-1 at T1 and T1) indicated that Tuntang Estuary was in the eutrophic condition. Based on the PI method, the water quality of Tuntang Estuary is good to slightly polluted for Class I, II, and III. The sustainable river management that is appropriate to be developed for the Tuntang River is conserving the mangrove ecosystem in the Tuntang Estuary.